Social-emotional competence among vocational students: A gender-based comparative study - Fayruziyah Ifroch Sabtana; Budi Astuti; M. Alvy Syahrin Mi’roj (Universitas Sebelas Maret, 2026)
This study aims to analyze differences in social-emotional competencies between female and male students in vocational high schools in West Nusa Tenggara. The background of this study is based on the assumption that gender studies in social-emotional competencies need to be approached critically, rather than simplified into assumptions of natural differences. This study employs a descriptive comparative quantitative method with a sample of 711 vocational students selected through simple random sampling. Data were analyzed using cross-tabulation and Mann–Whitney tests. The findings reveal that the majority of students are in the moderate category (67.4%), indicating that social-emotional competencies are present but not yet optimally developed, while 31.4% fall into the low category, reflecting a substantial proportion of students who still require targeted support. Statistical analysis shows significant gender differences in three SEL dimensions: self-awareness (p = 0.019), self-management (p = 0.000), and relationship skills (p = 0.036), suggesting that gender may influence how students develop and express specific social-emotional competencies. These findings highlight the need for more responsive and inclusive approaches to Social Emotional Learning (SEL) that consider gender-related differences without reinforcing stereotypes. Practically, this implies the importance of designing SEL interventions that are adaptive, equitable, and sensitive to diverse student needs in both instructional and counseling contexts.